CELLULAR INTEGRITY OF PEOPLE WITH LUNG OR HEAD AND NECK CANCER UNDERGOING A HOME-BASED PHYSICAL TRAINING PROGRAM DURING ONCOLOGICAL TREATMENT - Pozo, Karina Marcela Morro [UNESP]; Gobbo, Luís Alberto [UNESP]; Grigoletto, Isis [UNESP]; Marini, Elisabetta; Ramos, Ercy Mara Cipulo [UNESP] (Elsevier, 2025)
Background Lung and head cancer have high incidence and mortality rates. Chemotherapy and radiotherapy are widely used therapeutic modalities in cancer treatment, acting by destroying tumor cells. However, these treatments can also affect healthy cells, leading to adverse effects and damage to cellular integrity and function. Considering the difficulty of going to a training center, the immunosuppression of this population and the benefits of physical exercise in healthy people, home physical training can be a complement to cancer treatment. Objectives To evaluate the cell integrity of people with lung or head and neck cancer undergoing a home-based physical training program during cancer treatment. Methods People with primary lung or head and neck cancer were randomized into a training group (TG) and a control group (CG). The TG performed home-based physical training during cancer treatment. Aerobic training was performed through daily walks of at least 20 minutes, seven times a week, and resistance training of elbow flexion, knee flexion and extension with a green elastic band (2.3 kg of resistance), twice a week. The training time followed the duration of cancer treatment established individually by the oncologist. The CG performed only cancer treatment without any type of physical exercise. The groups were evaluated before and after cancer treatment, regarding the cell integrity (phase angle of the bioelectrical impedance analysis). The paired t-test was used to verify the intragroup difference and the independent t-test for intergroup analysis. In addition, a linear regression with the cell integrity and training adherence was performed. Results Fifty-four people were evaluated, most were diagnosed with head and neck cancer (60%), men (78%), with overweight and in an advanced stage of the disease (74%). The TG performed the home physical training program for a mean of 14 weeks, with 52% mean adherence. Both groups showed a decrease in the phase angle, but this decrease was significant only in the CG (TG = Baseline: 4.96 ± 0.68; Final: 4.72 ± 0.69; p = 0.060) (CG = Baseline: 5.05 ± 0.96; Final: 4.59 ± 0.82; p = 0.001), but there was no difference between the groups (p = 0.210). When stratifying the sample, a significant decrease in the CG was also observed in men (p = 0.005), people with lung cancer (p = 0.045), head and neck cancer (p = 0.016) and advanced stage cancer (p = 0.003). However, there was no statistical difference between groups. In addition, the linear regression demonstrated that greater adherence to home training (> 60%) was associated with a smaller reduction or better maintenance of the cell integrity. Conclusion People with lung or head and neck cancer who underwent home physical training during cancer treatment appear to have maintenance of cellular integrity, especially in individuals with greater adherence to physical training. Implications These findings highlight the potential of home exercise programs as a strategy to complement oncological care. Additionally, these results reinforce the need for healthcare policies that promote physical activity as an adjunct therapy in cancer care.